Clinical Course and Quality of Life in High-Risk Patients With Hypertrophic Cardiomyopathy and Implantable Cardioverter-Defibrillators. (April 2018) - Maron, Barry J.; Casey, Susan A.; Olivotto, Iacopo; Sherrid, Mark V.; Semsarian, Christopher; Autore, Camillo; Ahmed, Aisha; Boriani, Giuseppe; Francia, Pietro; Winters, Stephen L.; Giudici, Michael; Koulova, Anna; et al.
Abstract : Background: High-risk patients with hypertrophic cardiomyopathy (HCM) are identified by contemporary risk stratification and effectively treated with implantable cardioverter-defibrillators (ICDs). However, long-term HCM clinical course after ICD therapy for ventricular tachyarrhythmias is incompletely understood. Methods and Results: Cohort of 486 high-risk HCM patients with ICDs was assembled from 8 international centers. Clinical course and device interventions were addressed, and survey questionnaires assessed patient anxiety level and psychological well-being related to ICD therapy. Of 486 patients, 94 (19%) experienced appropriate ICD interventions terminating ventricular tachycardia/ventricular fibrillation, 3.7% per year for primary prevention, over 6.4±4.7 years. Of 94 patients, 87 were asymptomatic or only mildly symptomatic at the time of appropriate ICD interventions; 74 of these 87 (85%) remained in classes I/II without significant change in clinical status over the subsequent 5.9±4.9 years (up to 22). Among the 94 patients, there was one sudden death (caused by device failure; 1.1%); 3 patients died from other HCM-related processes unrelated to arrhythmic risk (eg, end-stage heart failure). Post-ICD intervention, freedom from HCM mortality was 100%, 97%, and 92% at 1, 5, and 10 years, distinctly lower than in ischemic or nonischemic cardiomyopathy ICD trials. HCM patients with ICD interventions reported heightened anxiety in expectation of future shocks, but with intact general psychological well-being and quality of life. Conclusions: In HCM, unlike ischemic heart disease, prevention of sudden death with ICD therapy is unassociated with significant increase in cardiovascular morbidity or mortality, or transformation to heart failure deterioration. ICD therapy does not substantially impair overall psychological and physical well-being. Abstract : Supplemental Digital Content is available in the text.